Do cryptocurrencies and crude oil influence each other? Evidence from wavelet-based quantile-in-quantile approach - Seyram Pearl Kumah; Jones Odei Mensah (Cogent Economics & Finance, 2022)
This study investigates the asymmetric shock transmission mechanisms between seven large cryptocurrencies and crude oil at different market conditions across time. Wavelet technique was used to decompose the daily return series of the assets into wavelet scales to capture trading horizons. We applied quantile regression (QR) and quantile-in-quantile Regression (QQR) on the decomposed series to capture the bear (bull) market conditions. Applying the QR, we found Ethereum, Steller, Ripple and Monero as hedges for oil market volatility at all market regimes from medium to long terms. The QR undermined the hedging properties of Bitcoin, Litecoin and Das, suggesting possible spread of market disruptions from these markets to crude oil market. We observe from QQR that the assets have negative influence on each other at bear market but positive influence at bull market across time, signifying hedging possibilities for both assets in bear market. The significance of our finding is strengthened by the recent rise in the market share of cryptocurrencies.
Keywords: C38; C58; E49; 330; Cryptocurrencies; crude oil; asymmetric effects; MODWT; quantile-in-quantile regression